Financial Reporting Quality, Investment Horizon, and Institutional Investor Trading Strategies - Bushee, Brian J.; Goodman, Theodore H.; Sunder, Shyam V. (The Accounting Review, 2019)
ABSTRACT This paper provides evidence that financial reporting quality (FRQ) influences the holding costs of trading strategies. While prior research has focused on the benefits of investment strategies based on poor FRQ (i.e., larger returns due to a greater amount of private information), we examine whether poor FRQ imposes greater holding costs on certain trading strategies. We show that poor FRQ motivates sophisticated investors with short-term horizons to tilt their portfolios away from value stocks, whose returns are contingent on investors revising their beliefs about firm fundamental value, and toward past winner stocks, whose future returns are realized more quickly. Poor FRQ also increases the length of time that institutions maintain large positions in value stocks. Our results imply that mis-valuations can be persistent when arbitrageurs perceive high holding costs from poor financial quality, even when they can see through the opaque financial disclosures.